Great cormorants reveal overlooked secondary dispersal of plants and invertebrates by piscivorous waterbirds - van Leeuwen, Casper H. A.; Lovas-Kiss, Ádám; Ovegård, Maria; Green, Andy J. (Biology letters (2005), 2017)
In wetland ecosystems, birds and fish are important dispersal vectors for plants and invertebrates, but the consequences of their interactions as vectors are unknown. Darwin suggested that piscivorous birds carry out secondary dispersal of seeds and invertebrates via predation on fish. We tested this hypothesis in the great cormorant (Phalacrocorax carbo L.). Cormorants regurgitate pellets daily, which we collected at seven European locations and examined for intact propagules. One-third of pellets contained at least one intact plant seed, with seeds from 16 families covering a broad range of freshwater, marine and terrestrial habitats. Of 21 plant species, only two have an endozoochory dispersal syndrome, compared with five for water and eight for unassisted dispersal syndromes. One-fifth of the pellets contained at least one intact propagule of aquatic invertebrates from seven taxa. Secondary dispersal by piscivorous birds may be vital to maintain connectivity in meta-populations and between river catchments, and in the movement of plants and invertebrates in response to climate change. Secondary dispersal pathways associated with complex food webs must be studied in detail if we are to understand species movements in a changing world.